Bio-hybrid scaffolds combining polyvinyl alcohol and decellularized articular cartilage for the treatment of focal chondral lesions in hemophilic patients - Barbon, Silvia; Confalonieri, Marta; Stocco, Elena; D’Osualdo, Alice; Contran, Martina; Parnigotto, Pier Paolo; De Caro, Raffaele; Todros, Silvia; Macchi, Veronica; Pavan, Piero G.; Porzionato, Andrea (Frontiers in Pharmacology, 2025)
IntroductionHemophilic arthropathy (HA) is a major complication of hemophilia, being caused by recurrent joint bleeding (hemarthrosis) which leads to iron accumulation in joints and subsequent damage to the articular cartilage (AC) and subchondral bone. Current treatments slow osteochondral degradation but do not promote cartilage regeneration. Tissue engineering offers a promising alternative for addressing AC damage in HA.MethodsThis study developed bio-hybrid scaffolds based on polyvinyl alcohol (PVA) combined with decellularized human AC to enhance bioactivity and mechanical support. AC was harvested from cadaveric donors and decellularized via a detergent-enzymatic protocol, with efficacy confirmed through DNA quantification, histomorphometric analyses and Scanning Electron Microsopy (SEM). The resulting decellularized AC matrix was then homogenized in acetic acid for combination with PVA. Bio-hybrid scaffolds were produced using two fabrication methods: a) cross-linking of a freeze-dried AC layer onto the PVA hydrogel, forming a double-layer structure and b) mechanical incorporation of homogenized decellularized AC into the PVA matrix. Bio-hybrid scaffold morphology, porosity, and mechanical properties were analyzed, and cytocompatibility was evaluated by seeding HM1-SV40 human mesenchymal stem cells (MSC) and assessing cell adhesion and growth by MTT assays and SEM after 7 and 14 days.ResultsQuality control studies on decellularized AC confirmed efficient cell/DNA removal and correct preservation of ECM components. Regarding the bio-hybrid scaffolds, SEM ultrastructural analysis revealed distinct surface roughness and porosity depending on the fabrication method. Compressive tests showed increased stiffness with higher PVA concentrations, while the addition of AC resulted in stiffness reduction, especially in the bilayer configuration. In parallel, consolidation tests revealed that PVA/AC_blend scaffolds showed similar short-term behavior to non-composite materials, while PVA/AC_bilayer exhibited a larger initial force drop, eventually aligning with PVA scaffolds at equilibrium. Cytocompatibility tests demonstrated that acellular AC matrix enhances PVA bioactivity, with PVA/AC_bilayer scaffolds better supporting cell adhesion and growth compared to PVA/AC_blend scaffolds.DiscussionThe findings underscore the potential of PVA/AC bio-hybrid scaffolds for cartilage regeneration in hemophilic patients affected by HA. These scaffolds combine mechanical integrity with enhanced cytocompatibility, representing a novel strategy in the context of tissue-engineered therapies for joint repair.